2022
DOI: 10.1111/jnc.15681
|View full text |Cite
|
Sign up to set email alerts
|

Plasma high‐density lipoprotein cargo is altered in Alzheimer's disease and is associated with regional brain volume

Abstract: Cholesterol levels have been repeatedly linked to Alzheimer's Disease (AD), suggesting that high levels could be detrimental, but this effect is likely attributed to Low-Density Lipoprotein (LDL) cholesterol. On the other hand, High-Density Lipoproteins (HDL) cholesterol levels have been associated with reduced brain amyloidosis and improved cognitive function. However, recent findings have suggested that HDL-functionality, which depends upon the HDL-cargo proteins associated with HDL, rather than HDL levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 113 publications
1
7
0
Order By: Relevance
“…Moreover, it has been previously described that ApoJ treatment could improve HDL functionality regarding atheroprotective, anti-oxidative and anti-inflammatory properties ( Rivas-Urbina et al, 2020 ). Also, ApoE in HDL could act as a protective factor since AD patients present HDL with lower ApoE content ( Pedrini et al, 2022 ), and in our previous study, we observed that subjects from an ICH-CAA cohort presented a higher ratio of ApoE/ApoC-III in HDL than controls which we hypothesized to be a defensive response against vascular Aβ deposition ( Bonaterra-Pastra et al, 2021 ). Higher circulating ApoE levels are known to be atheroprotective, and ApoE-enriched HDL are able to reduce CAA in an in vitro model ( Morton et al, 2019 ; Robert et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, it has been previously described that ApoJ treatment could improve HDL functionality regarding atheroprotective, anti-oxidative and anti-inflammatory properties ( Rivas-Urbina et al, 2020 ). Also, ApoE in HDL could act as a protective factor since AD patients present HDL with lower ApoE content ( Pedrini et al, 2022 ), and in our previous study, we observed that subjects from an ICH-CAA cohort presented a higher ratio of ApoE/ApoC-III in HDL than controls which we hypothesized to be a defensive response against vascular Aβ deposition ( Bonaterra-Pastra et al, 2021 ). Higher circulating ApoE levels are known to be atheroprotective, and ApoE-enriched HDL are able to reduce CAA in an in vitro model ( Morton et al, 2019 ; Robert et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…Alterations in Aβ production and clearance may cause a redistribution of Aβ from parenchyma to vasculature, possibly causing a lower burden of neuritic plaques together with a major accumulation of Aβ in the cerebral vessels, which could explain how protective factors for AD could cause risk for CAA and vice versa. However, these genes are also involved in many biological mechanisms that may differently influence both pathologies, such as Tau pathology or BBB integrity maintenance (Obermeier et al, 2013;Shulman et al, 2013;Beecham et al, 2014;Benitez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not take into account certain electrophysiological parameters of the participants, such as body mass index, blood pressure, blood lipids, and alcohol consumption, which have been shown to impact the volume of brain regions. 49 , 50 , 51 , 52 Finally, we did not investigate the relationship between cognitive functions, such as episodic memory and executive function, and the volume of specific subregion of the BF. We intend to include cognitive measures in future research to better understand how changes in BF volume correlate with cognition.…”
Section: Discussionmentioning
confidence: 99%
“… Subjects Substances Main finding Ref. AD patients Sphingomyelin, Ceramides, Cholesterol Esters, and 4-Hydroxynonenal A significant increase in cholesterol levels; sphingolipids and cholesterol are associated with oxidative stress in the normal aging process, accumulating in brain cells [ 49 ] AD patients Cholesterol The homeostasis of cholesterol in the AD brain is compromised; alterations in nuclear receptor levels or activity may contribute to cholesterol retention, which could enhance β and γ-secretase activities and the generation of Aβ [ 53 ] APP/PS1/SREBP-2 mice The cerebral homogenate and isolated mitochondrial total cholesterol Elevated cerebral cholesterol levels accelerate the activation of β-secretase, leading to the accumulation of Aβ, tau pathology, oxidative damage, and neuroinflammation [ 54 ] AD or MCI patients Serum TC, TG, LDL-C and HDL-C levels Serum TC and LDL-C levels are elevated [ 55 ] MCI patients Serum TC, LDL, HDL and TG The incidence of MCI is associated with middle-aged hypercholesterolemia [ 56 ] AD patients HDL The composition of HDL has undergone alterations, potentially impacting its functionality [ 66 ] AD patients Serum lipidomic parameters Serum levels of LDL-C and TC are associated with the risk of AD in Asian populations [ 57 ] Astrocyte-Ribotag Mouse mRNA of astrocytes Enzymes in the cholesterol synthesis pathway are downregulated in aging astrocytes, while cholesterol transport proteins are upregulated [ 59 ] AD patients Oxygenated sterol level...…”
Section: Regulation Of Cholesterol Homeostasis In Admentioning
confidence: 99%
“…However, some studies indicate that the quality of cholesterol-related molecules, rather than their levels, may be a key factor. In AD patients, the composition of high-density lipoprotein (HDL) (such as morphology, lipid and protein composition, and function) undergoes changes, which may affect the function of HDL, and this change is related to alterations in regional brain volume data [ 65 , 66 ]. The quality of HDL is also related to the degree of HDL modification, such as glycosylation and oxidation, which lead to the polymerization of ApoA-I and aggregation, resulting in the generation of amyloid-like proteins [ 65 , 66 ].…”
Section: Regulation Of Cholesterol Homeostasis In Admentioning
confidence: 99%